GANGGUAN FONOLOGI PADA ANAK USIA 4 TAHUN: KAJIAN PSIKOLINGUISTIK - Eka Edinda Yuliana Andriyani; Ananda Putri Prameswari; Sundawati Tisnasari (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study aims to describe the forms of phonological language disorders in a 4-year-old child with speech delay and to analyze their causes using a psycholinguistic approach. This research employed a qualitative method with a case study design. Data collection techniques included direct observation, recorded speech samples, and semi-structured interviews with the child’s parents. The findings revealed three main types of phonological disorders: lisping, slurring, and cluttering. Lisping is characterized by the substitution of difficult-to-articulate phonemes such as /k/, /r/, and /s/ with simpler sounds like /t/, /l/, and /c/, reflecting weak articulatory control and phonemic perception. Slurring involves the omission of initial phonemes or syllables due to poor motor coordination and limited phonetic stimulation. Meanwhile, cluttering is marked by disorganized sentence structure, rapid speech, and successive elisions, indicating a mismatch between verbal processing speed and speech production ability. These three disorders are closely related to neurological immaturity and the influence of language models in the surrounding environment. This study emphasizes the importance of early detection and customized speech therapy to support optimal language acquisition in children. Future research may explore culturally based intervention models and technology-assisted therapies to support language development in children with similar conditions.